2018
DOI: 10.1002/maco.201810036
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and corrosion behaviors of squeeze‐cast Mg‐4Al‐2RE and Mg‐4Al‐0.5RE‐xCa (x = 0.3, 0.8, and 1.5) alloys

Abstract: To develop low‐cost and ultrahigh strength magnesium alloys, AE42 (Mg‐4Al‐2RE) alloy is modified by adding Ca (Mg‐4Al‐0.5RE (RE = Y, Ce)‐xCa (x = 0.3, 0.8, and 1.5)) to replace the majority of rare earth elements. The microstructures of squeeze‐cast AE42 and Mg‐4Al‐0.5RE‐xCa alloys are investigated by XRD, EPMA, and SEM, respectively. The corrosion behaviors of all alloys are studied by gravimetric measurements and electrochemical tests. Results show that the microstructure difference between AE42 and Mg‐4Al‐0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The granular Al–RE phase was distributed in the magnesium alloy matrix. Al–RE phase potential was −1.44 V SCE , while the α‐Mg and β‐Mg 17 Al 12 phase were −1.66 and −1.20 V SCE , respectively . Thus, the microcell corrosion between Al–RE and α‐Mg phases was more difficult to occur than that between α‐Mg and β‐Mg 17 Al 12 phases.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The granular Al–RE phase was distributed in the magnesium alloy matrix. Al–RE phase potential was −1.44 V SCE , while the α‐Mg and β‐Mg 17 Al 12 phase were −1.66 and −1.20 V SCE , respectively . Thus, the microcell corrosion between Al–RE and α‐Mg phases was more difficult to occur than that between α‐Mg and β‐Mg 17 Al 12 phases.…”
Section: Resultsmentioning
confidence: 94%
“…However, the poor corrosion properties of magnesium alloys limit their wide applications . Al and rare earth (RE) are the most commonly used elements to improve the corrosion resistance of magnesium alloys . However, the Mg–Al–RE alloys exhibit poor stability at high temperature because of the presence of Al 11 RE 3 and Mg 17 Al 12 phases …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that in a humid atmosphere the surface of magnesium alloys can react to form a layer of thin film, which consists of magnesium oxide and magnesium hydrate. In addition, this naturally formed thin film can protect the alloy from corrosion at normal temperatures in the atmosphere without a corrosion medium . However, in the wet hydrogen sulfide atmosphere, the surfaces of the specimens easily form the absorbed electrolyte layers containing hydrogen sulfide, which can destroy the thin oxidation film, leading to the occurrence of pitting corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…When the volume fraction of secondary phases is sufficiently large and a continuous network of precipitated phases is formed, it can retard the corrosion process through a barrier mechanism [ 94 , 95 ]. As such, continuous secondary phases can inhibit the development of corrosion from one grain to another [ 96 ]. Furthermore, dual effects in precipitated phases can be affected by distribution morphology when the potential difference is small between the second phases and the Mg matrix.…”
Section: Corrosion Behaviormentioning
confidence: 99%